Dielectric Properties of Normal and Metastatic Lymph Nodes Ex Vivo From Lung Cancer Surgeries. Issue 2 (8th January 2020) - Yu, Xuefei; Sun, Ying; Cai, Kaican; Yu, Hongfeng; Zhou, Difu; Lu, Di; Xin, Sherman Xuegang
Abstract : The dielectric properties of normal and tumor human tissues have been widely reported in recent years. However, the dielectric properties of intrathoracic lymph nodes (LNs) have not been reported. In this communication, we measured the dielectric properties (i.e., permittivity and conductivity) of ex vivo intrathoracic LNs obtained from lung cancer surgeries. Results show that the permittivity and conductivity of metastatic LNs are higher than those of normal LNs over the frequency range of 1 MHz–4 GHz. Statistically significant differences are observed at single specific frequencies (64, 128, 298, 433, and 915 MHz and 2.45 GHz). Our study provides the basic data to support future‐related research and fills the research gap on the dielectric properties of LNs in the lungs. Bioelectromagnetics. 2020;41:148–155. © 2020 Bioelectromagnetics Society.